Prototype Sistem Monitoring Kebakaran Berbasis IoT Menggunakan Node MCU Dengan Penyemprot Air Otomatis - Lailia Rahmawati; Yoga Yusuf Pratama; Muhammad Gugus Azhari (Jurnal JEETech, 2022)
Fires are very detrimental, ranging from loss of property to even loss of life. Fires can be detected when the fire has grown or smoke has billowed out of buildings. Urban areas have densely populated housing so that it has the potential to cause problems in the event of a fire. These fires can be caused by by factors of human negligence and natural factors. Such as the occurrence of short-circuited electricity, negligence in cooking, negligence in burning garbage, and others. Therefore, we need a tool that can detect the presence of an early source of fire so that it does not spread. The problem that often occurs is when a fire occurs, the fire department often arrives late, so there are many losses due to the fire. And the losses can be material and economic. Therefore we need a system that works to control the fire automatically and to extinguish the fire in every house. This study aims to design and build an efficient and affordable prototype. Which later can be applied to housing or warehouses. This prototype is designed using NodeMCU ESP8266 as the main controller, Flame sensor can respond to infrared light beams on the modulation spectrum from 5 to 30 cycles per second, Web Thinger.Io as a server, data storage on the internet of things , and notification of fire in the Blynk application. This system uses a flame sensor based on the Node MCU ESP8266 microcontroller and is equipped with a Buzzer for Alarm and a Mini Water Pump to automatically spray water if a fire is detected. This system utilizes the Blynk Application as an interface to provide notification information about a fire to find out notifications if a fire is detected. And if a fire is detected, it will automatically get a notification from the Blynk application on the "There is Fire" Smartphone and the buzzer will automatically sound and the mini water pump will automatically spray water. In this study, the tool can automatically send Safe and Fire notifications using the blynk application on a smartphone with a delay of < 3 seconds.